We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
45
1
avatar+76 

F(x) = x^2 + 2x-6 

g(x) = x^4 +3 

enter your answer in the box 

(f.g) (x) = 

 Mar 10, 2019
 #1
avatar+4779 
+1

\((f.g)(x) = f(x) g(x)\\ \text{so just multiply the two polynomials together}\)

.
 Mar 10, 2019

9 Online Users